Ambulatory Physical Activity Profiles of Older Adults - Strath, Scott J. (2009)
This study examined objectively determined walking profiles of older adults across a wide range of sociocultural backgrounds. All individuals (N = 415; 131 men age 70.5 ± 9.2 yr and 284 women age 71.5 ± 9.0 yr) underwent physiological measurements, completed pen-and-paper surveys, and wore a pedometer for 7 consecutive days. The total sample accumulated a mean of 3,987 ± 2,680 steps/day. Age (r = −.485, p <.001) and body-mass index (BMI; r = −.353, p <.001) were negatively associated with steps per day. Multivariate analysis revealed that race/ethnic category (F = 3.15, df = 3), gender (F = 2.46, df = 1), BMI (F = 6.23, df = 2), income (F = 9.86, df = 1), education (F = 43.3, df = 1), and retirement status (F = 52.3, df = 1) were significantly associated with steps per day. Collectively these categories accounted for 56% of the variance in walking activity in this independently living, community-dwelling older adult sample. Sedentary characteristics highlighted within, and step-per-day values specific to, older adults have implications for planning targeted physical activity interventions related to walking activity in this population.